The Role Of Six Thinking Hats In Supporting The Design Thinking Ideation Stage In The Development Of Moringa Lesaf Cookies - Safa'atin, Haya Nur; Lafenia, Riska (AKSIOMA : Jurnal Manajemen, 2026)
This study aims to analyze the role of six thinking hats in supporting the ideation stage of design thinking for the development of moringa leaf cookies as an innovative functional food product. The method used for this study is qualitative with descriptive analysis using a design thinking framework consisting of the stages of empathize, define, ideate, prototype, and test. The results show that integrating six thinking hats in the ideation stage helps organize creative thinking, encourages diverse perspectives, and improves the quality of product ideas. The prototype of moringa leaf cookies is unique in terms of color and nutritional value. However, it still requires improvements in aspects of taste, aroma, and appearance. Based on the results of user acceptance tests, this approach has proven effective in supporting food product innovation that is oriented towards user needs.